The Effectiveness of Simulation in Education 4.0: Application in a Transesophageal Echocardiography Training Program in Malaysia - AwangHarun, Sakinah; Md Hashim, Noorjahan Haneem; Kadiman, Suhaini (Frontiers in Surgery, 2022)
Introduction A Malaysian Higher Education Provider has applied technology as part of its pedagogical approach, in alignment with Education 4. 0. The use of simulation, which aligns with the principles of Education 4.0, employs digital technologies and supports learning by bridging the classroom and the clinical areas. We reported the effectiveness of learning in our program that utilizes multimodal pedagogy, including interactive lectures, pre-recorded video lectures, simulation, and hands-on supervised clinical sessions, using the program's cumulative assessment data. Methodology This program evaluation was based on Kirkpatrick's framework. End-points for learning (Kirkpatrick level 2) were analyzed based on improved overall post-test theoretical and clinical assessment performance. Quantitative data analysis of theoretical pre-test, theoretical post-test, clinical assessment, and post-test scores was performed to compare cohorts. Results The performance of 19 trainees, over six cohorts from 2012 to 2019, were analyzed. All our trainees had equal opportunities to learn using the multimodal pedagogy, including a simulator. The analysis of pre- and post-theoretical test scores showed a significant improvement in the mean scores (pre-test 48.7% (± SD 9), post-test 64.1% (± SD11.5); p ≤ 0.001). Overall, 19 out of 21 trainees completed the clinical assessment and case presentation satisfactorily Conclusion The Kirkpatrick framework served as a useful framework to perform the evaluation of the TEE program. The significant improvement in post-test scores, when compared with pre-test scores, suggested that the program is effective with regard to learning. As part of a multimodal pedagogy, simulation has proven to be an added value to our training program, and this was reflected by the improvement in the clinical assessment scores when compared to the pre-test scores. This result aligned with the concept of technology-enhanced learning in Education 4.0, where simulation in TEE training is applicable in the Malaysian context.